The Effectiveness of Digital Textbooks on Brain-based Learning assisted by Animated Videos and Maze Chase-Wordwall on Science Literacy Skills and Student Learning Outcomes - Windari, Meylinda Retno; Prihatin, Jekti; Fikri, Kamalia (Biosfer: Jurnal Tadris Biologi, 2023)
This study aimed to determine the effectiveness of digital textbooks on Brain-based Learning assisted by animated videos and Maze ChaseWordwall to improve science literacy and learning outcomes of high school students. The media was developed using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research method used mixed methods, combining qualitative and quantitative methods. Based on the analysis results, digital textbooks on Brain-based learning assisted by animated videos and Maze ChaseWordwalls can effectively improve student learning outcomes and science literacy as indicated by the small-scale and large-scale class learning outcomes that obtained a high category with an N-gain value of 0.81. Furthermore, science literacy skills received an average score in the high category with a value of 86.ABSTRAK: Tujuan dari penelitian ini adalah untuk mengetahui keefektifan buku ajar digital berbasis Brain-based Learning yang dilengkapi dengan video animasi dan Maze Chase-Wordwall untuk meningkatkan literasi sains dan hasil belajar siswa SMA. Pengembangan media pada penelitian ini menggunakan model ADDIE (Analysis, Design, Development, Implementation, and Evaluation). Metode penelitian yang digunakan ialah penelitian kombinasi (mixed methods) yaitu gabungan metode kualitatif dan kuantitatif. Berdasarkan hasil penelitian, dapat dinyatakan bahwa buku ajar digital dengan Brain-based Learning menggunakan video animasi dan Maze Chase-Wordwalls secara efektif dapat meningkatkan hasil belajar dan literasi sains siswa yang ditunjukkan dengan kategori hasil belajar kelas skala kecil dan skala besar yang memiliki kategori tinggi dengan memiliki nilai N-gain sebesar 0,81, sedangkan hasil kemampuan literasi sains memperoleh skor rata-rata pada kategori tinggi dengan memiliki nilai sebesar 86.